Pengaruh penggunaan metode student facilitator and explaining dalam pembelajaran kooperatif terhadap kemampuan pemecahan masalah matematik siswa SMK di Kota Tasikmalaya - Siska Ryane Muslim (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2015)
This study was aimed at determing the effect of the use of Student Facilitator and Explaining type of cooperative learning model on students’ mathematical problem-solving. This study was an experiment, with the population of vocational school students in the city of Tasikmalaya. Sampling used was a random sampling, and it was selected two classes of grade X. The experimental group was treated by apllying cooperative learning model with Student Facilitator and Explaining method whereas the control class was direct instruction. Instruments used were test to assess mathematical problem solving abilities. The result of the study has been found that students’ mathematical problem solving abilities who participated by cooperative learning model with Student Facilitator and Explaining method are better than of  the group of students who participated in direct instruction. There were differences in the problem solving abilities of the top, middle, and lower groups of students who participated by the model of cooperative learning with Student Facilitator and Explaining methods.